A Juridical Review of Transgender Heirs from the Perspective of Islamic Law and Civil Law - Fathin, Fathiyyah Jamil; Koto, Ismail (Jurnal Hukum Replik, 2024)
This study aims to explore the legal status of transgender or transsexual heirs, the portion of inheritance they are entitled to, and legitimate strategies for addressing inheritance disputes. The research employs a normative juridical approach, utilizing a written survey procedure to analyze relevant legal frameworks. The findings reveal that, under Islamic law, transsexual individuals are typically viewed based on their biological sex prior to undergoing gender reassignment surgery, with differing interpretations across various schools of thought regarding their inheritance rights. Additionally, civil laws in different countries may influence how transsexual heirs are treated, depending on the legal and social context of each nation. Resolving inheritance issues involving transsexual individuals is often complex, due to the need for clarity regarding gender identity and the variation in legal perspectives. Overall, the understanding and application of inheritance laws concerning transsexuals are still evolving, underscoring the necessity for thoughtful reform to ensure equality in inheritance matters.Keywords: transgender, inheritance law, Islamic law, civil law